A Unified Database for a Set of Clinical Studies on the Treatment of Bacterial and Fungal Infections Within the MULTI-SITA Project...36th Medical Informatics Europe (MIE) Conference, May 25-28, 2026, Genoa, Italy. - ANTOLA, Stefano; GALLONE, Selene; MURGIA, Ylenia; GIACOBBE, Daniele Roberto; BASSETTI, Matteo; GIACOMINI, Mauro (Studies in Health Technology & Informatics, 2026)
The MULTI-SITA project, an observational pharmacological study involving 30 centers across Italy, required a flexible and scalable data management solution. This paper describes the transition from separate study-specific databases to a unified SQL Server-based system with a modular architecture and a web interface developed in Blazor Server. The new design enhances data interoperability, supports future studies, and simplifies clinician interaction, paving the way for future alignment with the OMOP Common Data Model.